Burn injury and long-term nervous system morbidity: A population-based cohort study - Vetrichevvel, T.; Randall, Sean; Fear, M.; Wood, F.; Boyd, James; Duke, J. (BM J Group, 2016)
Objective To investigate if children and adults who are hospitalised for a burn injury have increased long-term hospital use for nervous system diseases. Design A population-based retrospective cohort study using linked administrative health data from the Western Australian Data Linkage System. Participants Records of 30 997 persons hospitalised for a first burn injury in Western Australia during the period 1980–2012, and 123 399 persons who were age and gender frequency matched with no injury admissions randomly selected from Western Australia's birth registrations and electoral roll. Main outcome measures Admission rates and summed length of stay for nervous system diseases. Negative binomial and Cox proportional hazards regression modelling were used to generate incidence rate ratios (IRRs) and HRs with 95% CIs, respectively. Results After adjustment for demographic factors and pre-existing health status, the burn injury cohort had 2.20 times (95% CI 1.86 to 2.61) as many nervous system admissions and 3.25 times the number of days in hospital (95% CI: 2.28 to 4.64) than the uninjured cohort. This increase was found for those who had sustained burns during childhood (<15 years: IRR, 95% CI: 1.97, 1.49 to 2.61) and early to mid-adulthood (15–45 years: IRR, 95% CI: 2.70, 2.06 to 3.55) and older adults (≥45 years: IRR, 95% CI: 1.62, 1.33 to 1.97). Significantly elevated first-time postburn admissions were observed for children for 15 years postburn discharge (0–5 years: HR, 95% CI: 1.97, 1.75 to 2.22; 5–15 years: HR, 95% CI: 1.44, 1.28 to 1.63) and for adults 45 years and older at index burn for 5 years postburn only (HR, 95% CI: 1.72, 1.42 to 2.09). Conclusions Burn injury appears to be associated with increased nervous system-related morbidity for many years after burn injury. Further work into the mechanisms and possible treatments to reduce this morbidity are warranted in light of these findings.